2019
DOI: 10.2166/wh.2019.297
|View full text |Cite
|
Sign up to set email alerts
|

Variations in sensitivity to chlorine in Ecuador and US consumers: implications for community water systems

Abstract: Successful implementation of chlorination for disinfecting community water systems in developing countries faces obstacles, with rejection of chlorinous flavor as a significant factor. Determining consumers' abilities to accurately detect chlorine in treated water is important to identifying acceptable chlorination levels that are also effective for water disinfection. Chlorine detection sensitivity was tested in untrained Ecuadorian consumers with limited prior experience with chlorinated water and US consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…To include this study in the summary in Table 3, it is assumed that at the 4.0 mg/L Cl 2 concentration (maximum allowable EPA health standard), U.S. participants would be able to accurately taste chlorine. Since Stout et al 16 did not perform a threshold analysis, we calculated median thresholds as denoted by the "**" in Table 3. Sample sizes of the studies ranged from 10 participants per study group 10 to 123 participants per study group; 16 however, sample sizes between 40 and 50 participants per study group were the most common.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To include this study in the summary in Table 3, it is assumed that at the 4.0 mg/L Cl 2 concentration (maximum allowable EPA health standard), U.S. participants would be able to accurately taste chlorine. Since Stout et al 16 did not perform a threshold analysis, we calculated median thresholds as denoted by the "**" in Table 3. Sample sizes of the studies ranged from 10 participants per study group 10 to 123 participants per study group; 16 however, sample sizes between 40 and 50 participants per study group were the most common.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These results were in line with expectations that taste thresholds would be most similar to rural and less developed contexts like what was reported in Ecuador and Bangladesh, but differ enough that they also justify the need for site-specific taste threshold research. This study shares many similarities with Stout et al 16 [(1): included rural Indigenous groups, (2): have similar median taste threshold results, (3): have larger sample sizes than commonly reported in the literature, and (4): follow similar procedures and methodology]. However, our study was the only study to report actual best-estimate taste and acceptability thresholds and ranges of these thresholds for both Indigenous and non-Indigenous comparison groups of the same country.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study illustrated in a simplified way the perception of some residents regarding the need for cleaning and maintaining domestic water tanks, indicating the need to increase popular awareness about the quality of water consumed. Some authors found that people do not trust the quality of water coming to their homes, leading them to consume bottled water for direct ingestion, using tap water for hygiene and household cleaning 13 .…”
Section: Conditions Of Storage and Maintenance Of Household Tankmentioning
confidence: 99%